Complement system's role in cancer and its therapeutic potential in ovarian cancer - (:unkn) unknown (WILEY, 2018)
Cancer immunotherapy is a strong candidate for the long-awaited new edition to standard cancer therapies. For an effective immunotherapy, it is imperative to delineate the players of antitumour immune response. As an important innate immune system effector mechanism, complement is highly likely to play a substantial role in cancer immunity. Studies suggest that there may be two different states of complement that show opposing effects on cancer cells; a complement profile that has antitumour effects with low expression of membrane-bound complement regulator proteins (mCRPs), lytic membrane attack complex (MAC) concentration and moderate C5a concentration, and a complement profile that has protumour effects with high expression of mCRPs, sublytic MAC and high concentrations of C5a. One of the cancers that urgently require innovative therapeutic approaches is ovarian cancer, and complement has a potential to be a good target for this purpose. A combinatorial approach where the complement cascade is fine-tuned by inhibiting some of its activities while promoting the others can prove to be a fruitful approach. Herein, we will briefly discuss the cancer-immune system interaction and then present a discussion of complement system's role in tumour immunity and its therapeutic potential for ovarian cancer immunotherapy.
Keywords: MONOCLONAL-ANTIBODY THERAPY; REGULATORY T-CELLS; FACTOR-H; ANAPHYLATOXIN C5A; IMMUNE-SYSTEM; TUMOR-CELLS; GENE-EXPRESSION; CD59; ACTIVATION; PROTEINS